Environmental & architectural phenomenology. Vol. 18, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2007)
Vol. 18, No. 2, Spring 2007 (includes “items of interest,” “citations received,” book review of Phyllis Richardson's New Spiritual Architecture, and essays by Gwendolyn Scott & Scott Deaner).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals